2018
DOI: 10.11648/j.ajns.20180703.14
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Nursing Intervention of Postoperative Thirst in Patients after Laparoscopic Cholecystectomy

Abstract: Objective To explore the best method to relieve thirst in patients after laparoscopic cholecystectomy through comparison. Methods 60 patients after undergoing laparoscopic cholecystectomy were randomized into Q-tip group and spraying group. In the Q-tip group, warm boiled water-absorbing Q-tips were applied to embrocate the lips of patients and in the spraying group warm boiled water was sprayed into the oral cavity of the patients once per hour or given when needed within 6 hours after operation so as to comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
3

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 9 publications
0
2
0
3
Order By: Relevance
“…Although thirst is not normally considered an important issue during postoperative period, one must pay attention, considering its complexity and the fact that it is one of the most stressful and impetuous experiences in immediate postoperative period(IPP) [ 4 ].Thirst is a strong distressing sensation that suppresses all other sensations; patients complain about it often in the post-anesthesia care unit. Thirst affect sleep quality and increase anxiety in patients, which affects their life quality and thus raises concern from medical staff [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although thirst is not normally considered an important issue during postoperative period, one must pay attention, considering its complexity and the fact that it is one of the most stressful and impetuous experiences in immediate postoperative period(IPP) [ 4 ].Thirst is a strong distressing sensation that suppresses all other sensations; patients complain about it often in the post-anesthesia care unit. Thirst affect sleep quality and increase anxiety in patients, which affects their life quality and thus raises concern from medical staff [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Xiaolan et al found that the application of warm boiled water spray is more effective than a cotton swab moistened with warm boiled water to relieve thirst in patients after laparoscopic cholecystectomy. 24 Gulia et al, in a studies conducted with intensive care patients, found that a bundle application (cold wet oral swabs to wipe oral cavity and cold water mouth spray) was more effective on thirst and mouth dryness in patients compared to the control group (control group was not given any intervention). 25 Puntillo et al found that the use of bundle application (oral swabs and ice-cold water sprays, and menthol lip moisturizer) was more effective in relieving thirst and dry mouth than the control group (usual oral care).…”
Section: Discussionmentioning
confidence: 99%
“…Studi lain membuktikan pemberian spray air hangat lebih efektif untuk menurunkan rasa haus pasien pasca operasi laparaskopi. Pemberian swab di dalam rongga mulut dapat dengan mudah terjatuh dan menyebabkan aspirasi sedangkan pemberian spray lebih aman, dapat membasahi seluruh mukosa mulut dan merangsang sekresi saliva (Xiaolan, 2018). Penelitian lain tentang pemberian air dingin pada pasien pasca operasi lebih efektif menurunkan rasa haus dibandingkan dengan pemberian air dengan suhu ruang (Conchon & Fonseca, 2018).…”
Section: Pendahuluanunclassified
“…Prinsip pemberian spray air dingin yaitu melembabkan dan menyegarkan mukosa mulut sehingga tidak dianjurkan untuk diberikan melebihi petunjuk pemakaian yaitu sebanyak 2-3 ml setiap 30 menit sekali. Pemberian spray air dingin akan menyebabkan aspirasi bila digunakan secara berlebihan (Xiaolan, 2018).…”
Section: Pembahasanunclassified
See 1 more Smart Citation